Individual and organizational health literacies: moderating psychological distress for individuals with chronic conditions. - Li, Ang (Journal of Public Health, 2022)
Background People with chronic conditions experience high psychological distress. Methods Using the National Health Survey in Australia during 2017–18, the study assessed whether and which health literacies moderated the relationship between chronic conditions and psychological distress for diabetes, chronic kidney disease (CKD), cardiovascular disease (CVD), arthritis, other musculoskeletal conditions, asthma, other chronic lower respiratory diseases and cancer. Psychological distress was regressed on chronic diseases, health literacy domains and their interactions, controlling for demographic, socioeconomic and health factors. Results Of 5790 adults, 4212 (72.75%) aged 18–64; 846 (14.6%) had high or very high psychological distress, 1819 (31.4%) had diabetes, CKD or CVD, 2645 (45.7%) musculoskeletal conditions, and 910 (15.7%) lower respiratory conditions. Having sufficient information from healthcare providers was associated with the lowest level of psychological distress for CKD and cancer. Social support was associated with significantly lower levels of psychological distress for cardiovascular, musculoskeletal and lower respiratory conditions. Understanding health information was associated with the largest improvement in psychological distress for diabetes. Conclusions Higher health literacies were associated with reduced risks of psychological distress among individuals managing chronic conditions. Interventions for improving self-management and health inequalities should incorporate disease-specific health literacy enhancement strategies at individual and organizational levels.